2022
DOI: 10.1038/s41598-022-15378-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in-house quantitative ELISA for the evaluation of different Covid-19 vaccines in humans

Abstract: Reliable serological assays are needed to understand the real impact of COVID-19. In order to compare the efficiency of different COVID-19 vaccines used in the National Vaccination Program in Tunisia, we have developed a quantitative in-house ELISA. The ELISA is based on the ectodomain of the SARS-CoV-2 Spike Baculovirus recombinant protein. We used a panel of 145 COVID-19 RT-PCR positive serum samples and 116 pre-pandemic serum samples as a negative panel. The validation was carried out by comparison to four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Using a threshold of Anti-Spike-1-RBD antibody ≥ 100 U/mL as a correlate of COVID-19 protection [ 6 ], it is remarkable that 84.6% of subjects met 6-month threshold criterion. Of note, there is limited data regarding the clinical applicability of using this Elecsys Anti-SARS-CoV-2 S RBD assay and the implications of its semi-quantitative antibody levels as it relates to the degree of immunity or protection against COVID-19 in vaccinated individuals [ 8 ]. Our cohort had significant variability and rather broad range of Anti-Spike-1-RBD levels, which may reflect participant characteristics, co-morbidities influencing vaccine responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a threshold of Anti-Spike-1-RBD antibody ≥ 100 U/mL as a correlate of COVID-19 protection [ 6 ], it is remarkable that 84.6% of subjects met 6-month threshold criterion. Of note, there is limited data regarding the clinical applicability of using this Elecsys Anti-SARS-CoV-2 S RBD assay and the implications of its semi-quantitative antibody levels as it relates to the degree of immunity or protection against COVID-19 in vaccinated individuals [ 8 ]. Our cohort had significant variability and rather broad range of Anti-Spike-1-RBD levels, which may reflect participant characteristics, co-morbidities influencing vaccine responses.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the absence of standardized antibody assays remains challenging for direct study result comparison. Thus, a more standardized method of assessing SARS-CoV-2 humoral immunity and correlates of immune protection is needed; ongoing research is being conducted to establish international standards to interpret humoral immunity results using different testing platforms and units of measurement [ 8 ]. We excluded participants with prior or breakthrough COVID-19, so as not to bias immunologic assessments, which may inadvertently select for more optimal vaccine responses.…”
Section: Discussionmentioning
confidence: 99%
“…After screening 38 studies (Figure 1) and excluding 16 (Supplementary references), 22 studies were eligible (18 retrieved from the main search and another 4 retrieved from cited/citation searches). [3][4][5][6][7][8][9][10][11][12][13][14][22][23][24][25][26][27][28][29][30][31] 19 studies were published in peer-reviewed journals and 3 were preprints. Other studies screened in-depth and excluded are shown in Supplementary References along with the reason for exclusion.…”
Section: Eligible Studiesmentioning
confidence: 99%
“…The spike (S) and nucleoprotein (N) proteins were of particular emphasis, being the most immunogenic of the SARS-CoV-2 structural proteins ( 16 , 17 ). Since COVID-19 vaccines contain and elicit antibody responses to the spike protein, antibody responses against the spike protein are often used to evaluate vaccine immunogenicity ( 17 , 18 ). In addition, antibodies targeting the nucleoprotein imply infection and re-infection ( 19 ) in the absence of RT-PCR, as is often the case in low-resource settings in Sub-Saharan Africa, where there is inadequate coverage of molecular diagnostics ( 20 ).…”
Section: Introductionmentioning
confidence: 99%